Perfect maps in compact (countably compact) spaces - G. L. Garg; Asha Goel (International Journal of Mathematics and Mathematical Sciences)
In this paper, among other results, characterizations of perfect maps in compact Hausdorff(Fréchet, countably compact, Hausdorff) spaces are obtained.